Prostaglandins in the induction of labour – do we have the optimal substance, dose, and route of administration? Literature review - Mlodawski, Jakub; Mlodawska, Marta (Medical Studies/Studia Medyczne, 2021)
Induction of labour (IOL) is a procedure that reduces mortality and morbidity of the mother and the newborn in particular clinical settings. Currently the number of indications for this procedure is increasing; at the same time, intensive work is underway to optimize IOL in terms of duration, obstetric results, and costs. There are no universal standards regarding the optimal way to pre-induce patients in the case of unfavourable cervix, but prostaglandin analogues play an important role in this process. In this paper we discuss the physiological role of prostaglandins and review the current evidence-based literature on this topic, trying to find optimal substance, dose, and route of administration in pre-induction of labour in terms of effectiveness, obstetrical outcomes, and intrapartum complications.